Does Library Use Affect Student Attainment? A Preliminary Report on the Library Impact Data Project - Stone, Graham; Pattern, Dave; Ramsden, Bryony (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2011)
The current economic climate is placing pressure on UK Universities to maximise use of their resources and ensure value for money. In parallel, there is a continuing focus on the student experience and a desire that all students should achieve their full potential whilst studying at University. Internal investigation at the University of Huddersfield suggests a strong correlation between library usage and degree results, and also significant under-usage of expensive library resources at both school and course level. Data from over 700 courses using three indicators of library usage; access to e-resources; book loans and access to the library were matched against the student record system and anonymised. Initial findings highlighted that the correlation between library usage and grade had not yet been significance tested. In January 2011, the University of Huddersfield, together with partners at the Universities of Bradford; De Montfort; Exeter; Lincoln; Liverpool John Moores; Salford and Teesside were awarded JISC funding to prove the hypothesis that there is a statistically significant correlation across a number of universities between library activity data and student attainment. Academic librarians at Huddersfield are also working closely with tutors on a selected sample of courses to explore the reasons for unexpectedly low use of library resources. By identifying subject areas or courses which exhibit low usage of library resources, service improvements can be targeted such as: course profiling, to determine the particular attributes of each course and its students, which may affect library use; targeted promotion of resources at the point of need; raising tutor awareness of resources, particularly e-resources and current awareness services; review of the induction process; target information resources allocation, to ensure value for money; target staffing resources, to ensure that support for students is available at key times of the year. This paper will report on the initial findings of the project and whether the measurable targets have been achieved: Sufficient data are successfully captured from all partners; Statistical significance is proved for all data; The hypothesis is either wholly or partly proved for each data type and partner.